Air quality, nitrogen use efficiency and food security in China are improved by cost-effective agricultural nitrogen management - Guo, Yixin; Chen, Youfan; Searchinger, Timothy D.; Zhou, Mi; Pan, Da; Yang, Junnan; Wu, Liang; Cui, Zhenling; Zhang, Weifeng; Zhang, Fusuo; Lin Ma; Sun, Yele; et al. (Nature Food, 2020)
China’s gains in food production over the past four decades have been associated with substantial agricultural nitrogen losses, which contribute to air and water pollution, greenhouse gas emissions and damage to human health. Here, we explore the potential to improve agricultural production practices that simultaneously increase yields while addressing these environmental challenges. We link agronomic research with air quality modelling for an integrated assessment of four improved nitrogen management strategies: improved farm management practices with nitrogen use reductions; machine deep placement of fertilizer; enhanced-efficiency fertilizer use; and improved manure management. We find that simultaneous implementation of the four strategies provides the largest benefits, which include: reductions in PM2.5 concentrations and associated premature deaths; increases in grain yields and grain nitrogen use efficiency; reductions in NO3− leaching and runoff and greenhouse gas emissions. Total benefits of US\$30 billion per year exceed the US\$18 billion per year in costs. Our findings indicate that policies that improve farmers’ agricultural nitrogen management in China will improve both food security and public health while addressing multiple environmental challenges. Similar increases in attention on agricultural policy around the world are likely to provide large benefits in food security, environmental integrity and public health.